The Periodic Solutions of Discrete Nagumo Equation - 刘玉荣 刘曾荣 等 (Journal of Shanghai University, 2002)
In this paper,the dynamical behavior of coupled map lattics(CMLs) discretised from Nagumo equation was considered,and it was proved that there exist various periodic solutions in the CMLs.